An Indonesian Adaptation of the Bot Usability Scale Full Version (BUS-42) - Budiarti; Harry Budi Santoso; Martin Schrepp; Mira Suryani; Rizal Fathoni Aji; Baginda Anggun Nan Cenka; Erza Janitradevi Nadine; Dony Abdul Chalid (Jurnal Sistem Informasi, 2026)
The Bot Usability Scale (BUS-42) is a tool specifically designed to evaluate chatbot usability, yet it has not been extensively applied in Indonesian contexts. This study aimed to adapt the BUS for Indonesian users, following Beaton’s cross-cultural adaptation framework to ensure cultural and linguistic relevance. The Indonesian adaptation was tested with 103 participants from the Faculty of Computer Science at one of large public universities in Indonesia, resulting in a high Cronbach’s Alpha of 0.922, confirming strong internal consistency. The adapted BUS-42 covers various usability attributes, including ease of use, accessibility, and response speed, making it suitable for assessing chatbot usability in academic settings. Findings suggest that the Indonesian-adapted BUS-42 is a reliable and comprehensive tool, applicable to different domains beyond education, such as e-commerce and government services. Future research should focus on extending BUS-42 testing to diverse chatbot applications and performing validity and sensitivity analyses to optimize its utility across various Indonesian user contexts.